Fat quality of ready to eat foods without nutritional label from unorganized sector: FAT QUALITY OF READY TO EAT FOODS WITHOUT NUTRITIONAL LABEL FROM UNORGANIZED SECTOR - APARNA KUNA; M SREEDHAR; C H JAGAN; D SHARANYA RANI; M BHAGYAMMA; V SANDHYA (Journal of Oilseeds Research, 2020)
The aimofthis studywas to investigate total fat and fatty acid composition in processed foods fromunorganized sector (without nutritional labels), with emphasis on trans fatty acid (TFA) content. A total of 41 products, divided into 5 categories, viz., salted snack foods (n=9), sweets (n=7), street foods (n=10), meal items (n=4) baked foods (n=11) were sampled for estimation of fatty acid composition. Results indicate mean total fat content in all foods ranged between 16.88 to 30.64%, with high saturated (36.14 to 58.20%) and trans fat content (1.18 to 3.40%). Palmitic acid (C16:0) was the highest fatty acid varying between 17.01% - 46.80% in all the processed foods, followed by Oleic acid (C18:2, n6cis). Elaidic acid (C18:1, n9trans), Linolelidic acid (C18:2, n6trans) and Vaccenic acid (C18:1, n11trans) were the trans fatty acids found in 93% of all the foods estimated. The quality of fats in most of the foods analyzed was found to be unhealthy due to high TFA content, which is a possible contributing risk factor for diet-related non-communicable diseases, and the consumers are unaware of the fat quality due to absence of nutritional labels.